Effectiveness of an Interventional Program on Nurses’ knowledge about Applying Guideline of Continuous Renal Replacement Therapy - Layth Abbas Khamees; Hussein Hadi Atiyah (Migration Letters, 2023)
Objectives: The main objective of this study is to determine the effectiveness of an educational program on the knowledge of nurses regarding the application of the guideline on continuous renal replacement therapy in the intensive care unit and the hemodialysis unit. Methodology: A quasi-experimental study was conducted with the application of the pre-test and post-test approach to the study group and the control group after applying the educational program. Data were collected in two phases: first baseline data (before any intervention presented to the study group) and then 21 days (after the program was administered education in the study group). The study period was from March 15th, 2022, to October 15th, 2022. Data were analyzed by using SPSS version 23. Results: The results of this study showed that there was a significant difference between the pretest and the posttest responses in the study group knowledge after application of the educational program, while there was a small difference between the pretest and the posttest in the control group. In addition, there were significant correlations between the age, level of education and number of training sessions with the knowledge of nurses. Conclusions: The results of the nurses’ knowledge regarding application of the guideline on continuous renal replacement therapy improved after implementing the educational program in the study group. Recommendations: The study recommended that the interventional program can be implemented for all nurses working in ICU and dialysis units to be prepared and competent with applying standards of CRRT. Moreover, efforts should be targeted toward employing nurses with higher degrees to deliver care for AKI patients who need CRRT. In addition, a standard guideline should be prepared and distributed for all nurses working in ICU and dialysis unit to be followed and applied to deliver required care for patients with CRRT.